Genetics and Molecular Biology of the Electron Flow for Sulfate Respiration in Desulfovibrio - Keller, Kimberly L.; Wall, Judy D. (Frontiers in Microbiology, 2011)
Progress in the genetic manipulation of the Desulfovibrio strains has provided an opportunity to explore electron flow pathways during sulfate respiration. The function of hydrogen production and consumption during oxidation of organic acids with sulfate as electron acceptor prompted the formulation of the hydrogen cycling model by Odom and Peck (FEMS Microbiol. Lett. 12:47-50, 1981). Examination of this model by many laboratories has generated conflicting results. Recent application of molecular genetic tools for the exploration of the metabolism of Desulfovibrio vulgaris Hildenborough has provided several new datasets that might provide insights and constraints to the electron flow pathways. These datasets include 1) gene expression changes measured in microarrays for cells cultured with different electron donors and acceptors, 2) relative mRNA abundances for cultures grown with lactate plus sulfate, and 3) a random transposon mutant library selected on lactate plus sulfate medium. Studies of directed mutations eliminating apparent key components, the quinone-interacting membrane-bound oxidoreductase (Qmo) complex, the Type 1 tetraheme cytochrome c3 (Tp1- c3), or the Type 1 cytochrome c3:menaquinone oxidoreductase (Qrc) complex, suggest a greater flexibility in electron flow than previously considered. The new datasets revealed the absence of random transposons in the genes encoding an enzyme with homology to CO-induced membrane-bound hydrogenase. From this result, we infer that Coo-hydrogenase plays an important role in D. vulgaris Hildenborough growth on lactate plus sulfate. These observations along with those reported previously have been combined in a model showing dual pathways of electrons from the oxidation of both lactate and the intermediate pyruvate during sulfate respiration. Continuing genetic and biochemical analyses of key genes in Desulfovibrio strains will allow further clarification of a general model for sulfate respiration.